2008
DOI: 10.1094/mpmi-21-5-0525
|View full text |Cite
|
Sign up to set email alerts
|

A Putative MAP Kinase Kinase Kinase,MCK1, Is Required for Cell Wall Integrity and Pathogenicity of the Rice Blast Fungus,Magnaporthe oryzae

Abstract: Insertional mutagenesis of Magnaporthe oryzae led to the identification of MCK1, a pathogenicity gene predicted to encode mitogen-activated protein kinase kinase kinase (MAPKKK) homologous to BCK1 in Saccharomyces cerevisiae. Targeted disruption of MCK1 resulted in the fungus undergoing autolysis and showing hypersensitivity to cell-wall-degrading enzyme. The mck1 produced significantly reduced numbers of conidia and developed appressoria in a slightly retarded manner compared with the wild type. Appressorium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(152 citation statements)
references
References 37 publications
9
137
1
Order By: Relevance
“…By contrast, Co Atg26 lacking the CAT region (ATG26DCAT) or Co Atg26 lacking PBD (ATG26DPBD) failed to increase the sensitivity of the atg26 mutant to glycerol, indicating that this appressorial phenotype correlates strongly with the defect in appressorial pexophagy (Figures 9D and 6B). A similar phenotype was also found in the appressoria formed by the mck1 mutant of M. oryzae, defective in the mitogen-activated protein kinase pathway for cell wall integrity (Jeon et al, 2008). These findings suggest that Atg26-mediated pexophagy is involved in certain structural aspects of appressorial development, which are subsequently important for efficient host invasion.…”
Section: Atg26-mediated Pexophagy and Appressorial Functionalitysupporting
confidence: 65%
“…By contrast, Co Atg26 lacking the CAT region (ATG26DCAT) or Co Atg26 lacking PBD (ATG26DPBD) failed to increase the sensitivity of the atg26 mutant to glycerol, indicating that this appressorial phenotype correlates strongly with the defect in appressorial pexophagy (Figures 9D and 6B). A similar phenotype was also found in the appressoria formed by the mck1 mutant of M. oryzae, defective in the mitogen-activated protein kinase pathway for cell wall integrity (Jeon et al, 2008). These findings suggest that Atg26-mediated pexophagy is involved in certain structural aspects of appressorial development, which are subsequently important for efficient host invasion.…”
Section: Atg26-mediated Pexophagy and Appressorial Functionalitysupporting
confidence: 65%
“…In M. oryzae, MPS1 and BCK1, putative orthologs of yeast Slt2 and Bck1, are important for fungal cell wall integrity and pathogenesis (Xu et al, 1998;Jeon et al, 2008). In this study, we showed that phosphorylation of Mps1 was reduced in the tig1, set3, and snt1 mutants ( Figure 9).…”
Section: Discussionmentioning
confidence: 53%
“…It is also essential for root infection (Sesma and Osbourn, 2004) and the proper regulation of the mobilization of storage carbohydrate and lipid reserves from conidia to appressoria (Thines et al, 2000). The other MAP kinase pathway essential for pathogenesis in M. oryzae is the MPS1 cascade, which is dispensable for appressorium formation but required for appressorial penetration (Xu et al, 1998;Jeon et al, 2008;Mehrabi et al, 2008). These two pathways also have been shown to be important for plant infection in other phytopathogenic fungi, including some species that do not form appressoria (Rispail et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Following epistasis study, Mor-Bck1 was suggested to function upstream of Mor-Slt2 to ensure proper appressorium function (Jeon et al, 2008). Two nuclear localized proteins from M. oryzae were also found to interact with Slt2 and are believed to act as key downstream substrates mediating MAPK function (Mehrabi et al, 2008;Qi et al, 2012).…”
Section: Slt2-type Mapks In Phytopathogenic Fungimentioning
confidence: 99%